Pre-service teachers' perception of their competence and their readiness for teaching profession - Lou Chien Gita Arista; Junaidi Mistar; Muthmainnah Mustofa; Dzulfikri Dzulfikri (English Education Journal, 2022)
The Indonesian Government takes serious measure on the future prospect of the teacher education graduates who are considered not to have a standardized competence ability to become a professional teacher. It inflicted some responses that opposed with the implementation of the program. This issue highlights the need for a more thorough investigation on the legitimacy of new teachers in Indonesia, as well as their quality. The goal of this study is to learn about pre-service teachers’ perceptions of their own competency and readiness to teach. This quantitative study used internet-based questionnaires to collect the data. The participants were 67 undergraduate students of university in Lamongan, East Java Province. The result of this research showed that p value (.258) is higher () than ɑ value (.05). It means that there were no correlation between pre-service teachers’ perception of their competence and their readiness for teaching profession. Nevertheless, the pre-service teachers have a positive perception regarding their competence and readiness to teach in a professional setting. By realizing and considering their competence and readiness for the teaching profession, they willfeel more confident and ready to face the real environment of teaching as a profession.